2018
DOI: 10.1016/j.cattod.2017.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transfer hydrogenolysis of organosolv lignin using B-containing FeNi alloyed catalysts

Abstract: In this work, FeB, NiB, and FeNiB nanomaterials were examined as catalysts for catalytic transfer hydrogenolysis (CTH) using supercritical ethanol (sc-EtOH) as the hydrogen donor and reaction solvent. The earth-abundant alloys were synthesized using simple aqueous chemical reductions and characterized using ICP-OES, XRD, and STEM-EDS. Using acetophenone to model the desired catalytic reactivity, FeNiB was identified as having superior reactivity (74% conversion) and selectivity for complete deoxygenation to et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Also, at 400 • C, the Fe can be much more easily reduced to Fe 0 for Ni-Fe/AC. The same phenomenon was observed for FeNiB catalyst during the hydrogenolysis of acetophenone, where 74% conversion yield was observed (NiB = 23%, FeB = 42%) [116]. Compared with other zeolite supports such as HZSM-5, MAS-7, MCM-41, and SAPO-11, H-Beta was found to have the highest acidity (1.3 mmol/g).…”
Section: Ni-based Bimetallic Catalysts For Hydrogenolysis Of Ligninsupporting
confidence: 72%
“…Also, at 400 • C, the Fe can be much more easily reduced to Fe 0 for Ni-Fe/AC. The same phenomenon was observed for FeNiB catalyst during the hydrogenolysis of acetophenone, where 74% conversion yield was observed (NiB = 23%, FeB = 42%) [116]. Compared with other zeolite supports such as HZSM-5, MAS-7, MCM-41, and SAPO-11, H-Beta was found to have the highest acidity (1.3 mmol/g).…”
Section: Ni-based Bimetallic Catalysts For Hydrogenolysis Of Ligninsupporting
confidence: 72%
“…As imilars tudy by Chmely et al showedt hat bimetallic FeNi alloyed catalysts were active for tandem dehydrogenation of 2-PrOH and fragmentation of organosolv lignin. [74] Using acetophenonea samodel compound, they further confirmed that the presenceo fBspeciesc ould promoteh ydrogenation of C=Ob onda nd CÀOc leavage. Therefore, both the bimetallic center (depolymerization) and catalytic promoter (hydrogenation) are required for the CTH-II of lignin feedstocks.…”
Section: Bimetallic Catalystsmentioning
confidence: 82%
“…A similar study by Chmely et al. showed that bimetallic FeNi alloyed catalysts were active for tandem dehydrogenation of 2‐PrOH and fragmentation of organosolv lignin . Using acetophenone as a model compound, they further confirmed that the presence of B species could promote hydrogenation of C=O bond and C−O cleavage.…”
Section: Case Study D: Lignin and Bio‐oil Upgradingmentioning
confidence: 99%
“…Despite that eucalyptus is a hardwood feedstock, the use of phosphate catalysts selectively produced only syringol with yield of 8.47% over β-CaP 2 O 6 and 6.67 % over CoP 2 O 6 . The hydrogenolysis of organosolv lignin from hybrid poplar in supercritical ethanol at 320 • C, by the use of amorphous B-containing FeNi alloyed catalysts, resulted in lignin depolymerization and the production of deoxygenated aliphatic side chains [136].…”
Section: Organosolv Ligninsmentioning
confidence: 99%